First estimates of batch fecundity for Parapercis colias , a commercially important temperate reef fish - NA Beer; SR Wing; G Carbines (New Zealand Journal of Marine and Freshwater Research, 2013)
Accurate fecundity information is essential for the sustainable management of exploited populations. Mounting evidence of strong size and age effects on female fecundity and egg characteristics indicates that, for spatially‐structured populations, management models should incorporate demographic information. Parapercis colias , a commercially important temperate reef fish, appears to form spatially structured populations at the mesoscale, but the current lack of understanding of spawning and reproductive behaviour could undermine efforts to protect populations from localised depletion. Here we present the first estimates of batch fecundity for P. colias , and initial suggestions of a relationship between fecundity and maternal characteristics that provide strong justification for further targeted research to understand this aspect of P. colias biology and the potential implications for future management.